2012
DOI: 10.1111/j.1742-1241.2012.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

The psychopathological characteristics of treatment discontinuation group in 6-month treatment with paliperidone ER

Abstract: Patients who discontinued early from a 6-month treatment period with Paliperidone have some characteristic differences compared with completion patients. Many factors including frequent hospitalisations, female gender, high PANSS score (indicating more disease severity) and previous exposure to first generation of antipsychotic agent might lead patients to discontinue from treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…No unexpected tolerability finding was observed. The overall discontinuation rate of this study is consistent with other recent published articles 1719. The percentage of patients discontinuing due to adverse events was relatively low (7.5%).…”
Section: Discussionsupporting
confidence: 91%
“…No unexpected tolerability finding was observed. The overall discontinuation rate of this study is consistent with other recent published articles 1719. The percentage of patients discontinuing due to adverse events was relatively low (7.5%).…”
Section: Discussionsupporting
confidence: 91%
“…This study is a part of the Paliperidone ER Functionality, Efficacy and Tolerability (PERFEcT) Study, a 6-month, open-label, multicenter, multi-country, prospective trial to explore the safety, efficacy, and functionality of paliperidone extended-release tablets. 17 The current study included only the baseline data obtained from Thai participants. The study was approved by the Ethics Committee or the Institution Review Board of each participating site.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with previous results that showed that schizophrenia patients with higher PANSS scores have a greater response to antipsychotics than those with lower PANSS scores. 11 …”
Section: Discussionmentioning
confidence: 99%